Procedure for Identifying Negative Emotional States in Military Personnel - Kudaibergenova, Sandugash; Madaliyeva, Zabira; Baimoldina, Laura; Sadykova, Nazira; Sadvakassova, Zukhra (Bangladesh Journal of Medical Science, 2023)
Objective: The development of a paradigm for enhancing the emotional state of service members and a method for identifying their negative states as a result of psychological stresses is of the utmost importance in the context of today’s pressing issues. To that end, the purpose of this study is to develop and subjectively test the effectiveness of a procedure for identifying negative emotional states in service members (cadets from Kazakhstan’s military institutes). Materials and methods: A two-stage procedure is proposed to identify a risk group for negative emotional states. The methodology for identifying negative emotional states is divided into two stages: screening and deep. Results and discussion: It will be discussed how the algorithm performed when tested on a sample of cadets from two military universities in Kazakhstan. According to the results, nearly all the people in the sample studied (approximately 95%) exhibited relatively positive indicators of psychological health, including low levels of depression, aggression, and anxiety. Negative emotional states were present in 5% of the service members. Additional ongoing dynamic assessment and monitoring of the risk group is required. Conclusion: The obtained results provide sufficient evidence to discuss how the proposed algorithm could be used. The research has practical value because it can be used to implement the applied method at training ranges in the contemporary military era. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 573-584